Uncovering Syntactic Features of Student Writing: A Case Study Of Weekly Journals - Jauhar Helmie; Vina Nuviyani; Siti Vega Nurintan (Fakultas Sastra - Universitas Muslim Indonesia, 2025)
Teaching syntactic unit especially clause to students is a crucial issue because clause is an important part in sentence forming. This research focuses on clause patterns that is a part of syntax which is needed by students in improve their ability in English (Basri, Ampa, & Junaid, 2013). This research adopts qualitative descriptive method to analyze seven English clause patterns in students’ weekly journal syntactically. The aims of this study are to know and analyze the types of clause pattern the students use in their weekly journal; to get information about the type of clause pattern that is frequently used by students in their weekly journal; and to gain the data about the way the students write the clause pattern in their weekly journal. This study took place in one of the vocational high schools in Cianjur by involving 32 students from XI AKKUL class. The data were gained from students’ weekly journal entitled Weekly Diary from September 23rd to November 13th 2018. The findings show clause pattern S+V is written in 15 data (6,91%), clause pattern S+V+O is written in 38 data (17,51%), clause pattern S+V+Co is written in 69 data (31,8%), clause pattern S+V+O+O is written in 3 data (1,38%), clause pattern S+V+O+Co is written in 25 data (11,52%), clause pattern S+V+Ad is written in 18 data (8,3%), and clause pattern S+V+O+Ad is written in 49 data (22,58%). From the data collected, it can be seen that the students tend to write their clause with S+V+Co pattern. The students like giving a complement for the subject in their clauses and mostly in form of adjective.